Unilateral paravertebral block compared with subarachnoid anesthesia for the management of postoperative pain syndrome after inguinal herniorrhaphy: a randomized controlled clinical trial. Issue 5 (May 2016) - Fusco, Pierfrancesco; Cofini, Vincenza; Petrucci, Emiliano; Scimia, Paolo; Paladini, Giuseppe; Behr, Astrid U.; Gobbi, Fabio; Pozone, Tullio; Danelli, Giorgio; Di Marco, Mauro; Vicentini, Roberto; Necozione, Stefano; et al.
Abstract : Abstract: Inguinal herniorrhaphy is a common surgical procedure. The aim of this investigation was to determine whether unilateral paravertebral block could provide better control of postoperative pain syndrome compared with unilateral subarachnoid block (SAB). A randomized controlled study was conducted using 50 patients with unilateral inguinal hernias. The patients were randomized to receive either paravertebral block (S group) or SAB (C group). Paravertebral block was performed by injecting a total of 20 mL of 0.5% levobupivacaine from T9 to T12 under ultrasound guidance, whereas SAB was performed by injecting 13 mg of 0.5% levobupivacaine at the L3 to L4 level. Data regarding anesthesia, hemodynamic changes, side effects, time spent in the postanesthesia care unit, the Karnofsky Performance Status, acute pain and neuropathic disturbances were recorded. Paravertebral block provided good anesthesia of the inguinal region without patient or surgeon discomfort, with better hemodynamic stability and safety and with a reduced time to discharge from the postanesthesia care unit compared with SAB. During the postsurgical and posthospital discharge follow-ups, rest and incident pain and neuropathic positive phenomena were better controlled in the S group than in the C group. The consumption of painkillers was higher in the C group than in the S group throughout the follow-up period. Paravertebral block can be considered a viable alternative to common anesthetic procedures performed for inguinal hernia repair surgery. Paravertebral block provided good management of acute postoperative pain and limited neuropathic postoperative disturbances. Abstract : Paravertebral block can be considered a viable anesthetic procedure for herniorrhaphy, and it could control acute postoperative pain syndrome and limit neuropathic postoperative disturbances.